Efficacy of Date Palm Pollen in the Male Sexual Dysfunction after Coronary Artery Bypass Graft: A Randomized, Double-Blind, Clinical Trial. (28th March 2022) - Hooshang, Hamed; Farahani, Ali Vasheghani; Rezaeizadeh, Hossein; Forouzannia, Seyed Khalil; Alaeddini, Farshid; Ashraf, Haleh; Karimi, Mehrdad
Abstract : Background . Bypass graft surgery of the coronary artery has a significant effect on the creation and development of sexual dysfunction among male patients. The previous studies have demonstrated that date palm pollen (DPP) increases the count and quality of sperm. Additionally, it has been shown that DPP has a protective effect against myocardial infarction and cardiac remodeling. Therefore, this is the first study investigating the impact of DPP ( Phoenix dactylifera L. ) on managing male sexual dysfunction after coronary artery bypass graft. Methods . This randomized, double-blind, placebo-controlled clinical trial was conducted on 60 patients (DPP group n  = 30, control group n  = 30) of Iranian men after coronary artery bypass graft. Two parallel groups were randomly generated from the study participants. The intervention group was prescribed 3 grams of the powder of DPP twice a day (9 AM and 9 PM) for two months, while the control group received the same prescription of the placebo powder. Results . The DPP consumption significantly increased the International Index of Erectile Function (IIEF) (from 23.21 to 46.57) and the Hurlbert Index of Sexual Desire (HISD) (from 59.39 to 64.45) scores over time in the intervention group. However, there were no significant changes in the control group. Conclusion . Daily intake of 6 g DPP for two months exhibited beneficial effects on the symptoms of male sexual dysfunction in patients who have undergone coronary artery bypass graft (CABG).